Biophysical determinants of front-crawl swimming at moderate and severe intensities - Ribeiro, J.; Toubekis, A. G.; Figueiredo, P.; de Jesus, K.; Toussaint, H. M.; Alves, F.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To conduct a biophysical analysis of the factors associated with front-crawl performance at moderate and severe swimming intensities, represented by anaerobic-threshold (vAnT) and maximal-oxygen-uptake (vV.O2max) velocities.